The Sociology of Intellectuals : After 'The Existentialist Moment' - Susen, Simon; Baert, Patrick (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book offers an unprecedented account of recent and future developments in the sociology of intellectuals. It presents a critical exchange between two leading contemporary social theorists, Patrick Baert and Simon Susen, advancing debates at the cutting edge of scholarship on the changing role of intellectuals in the increasingly interconnected societies of the twenty-first century. The discussion centres on Baert's most recent contribution to this field of inquiry, The Existentialist Moment: The Rise of Sartre as a Public Intellectual (2015), demonstrating that it has opened up hitherto barely explored avenues for the sociological study of intellectuals. The authors also provide an overview of various alternative approaches that are available for understanding the sociology of intellectuals, such as those of Pierre Bourdieu, Randall Collins and Neil Gross. In doing so, they grapple with the question of the extent to which intellectuals can play a positive and empowering role in shaping the current and future development of society. This insightful book will appeal to students and scholars of the humanities and social sciences, particularly to those interested in social theory and the history of intellectual thought.